Potential Impact of Investment Agreements in Post-Assad Syria - Koman, Munaff; Mehchy, Zaki (University of Edinburgh, LSE CCRG, 2025)
This policy brief highlights the structure, drivers, and potential impact of post-Assad investment agreements in Syria, based on the analysis of 111 publicly reported economic events and agreements between April and September 2025. It indicates that direct investment is critical for economic recovery, yet most of these agreements are shaped by political considerations rather than developmental priorities. The predominance of rent-seeking sectors, lack of transparency, weak institutional oversight, and the exclusion of local voices risk reinforcing pre-conflict patterns of inequality, cronyism and corruption. The brief concludes with recommendations focusing on institutional reform and participatory planning to ensure that investment inflows contribute to an inclusive or sustainable recovery.
Keywords: Syria